Answer:
Y-intercept;
(0, 1)
Asymptote;
Horizontal asymptote: y = -2
Explanation:
We have been given the following exponential function;
![f(x) = 3^(x+1)-2](https://img.qammunity.org/2020/formulas/mathematics/high-school/u5v2q0f1jq0dfmmb0ha0cf0dle9dx0n336.png)
The y-intercept of a function is the point where the graph of the function intersects the y-axis. At this point, the value of x is usually 0. Therefore, to establish the y-intercept of the given function we substitute x with 0 in the given equation and simplify;
![y=3^(0+1)-2\\ \\y=3-2=1](https://img.qammunity.org/2020/formulas/mathematics/high-school/rgxgpk82pky1w032gibrs2yx9bafidkgcm.png)
The y-intercept of the given function is thus (0, 1).
Exponential function of the form;
![f(x)=c.n^(ax+b)+k](https://img.qammunity.org/2020/formulas/mathematics/high-school/fw1q0gv0je7vzfjzsyn61i82yki8kb9zey.png)
has a horizontal asymptote y = k. In the function given, k = -2 implying that
y = -2 is a horizontal asymptote of the given exponential function